Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.mr000032
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to reduce attrition in randomised trials

Abstract: Attrition from randomised trials can introduce bias and reduce study power affecting the generalisability, validity, and reliability of results [1]. Many strategies are used by trialists to reduce attrition, including motivating and engaging participants and sites to optimise data return or compliance to follow-up procedures [2]. Objective To quantify the effect of strategies to reduce attrition from randomised trials in any healthcare setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…This was important as CPIT participants and others who had participated in incentive schemes were generally more positive about incentives and their delivery processes than those with no experience of incentive interventions. This is encouraging as incentives can reduce attrition in intervention trials 216 and, once engaged, voucher incentive interventions for smoking cessation in pregnancy are both effective and acceptable to participants.…”
Section: Strengths and Limitationsmentioning
confidence: 98%
See 3 more Smart Citations
“…This was important as CPIT participants and others who had participated in incentive schemes were generally more positive about incentives and their delivery processes than those with no experience of incentive interventions. This is encouraging as incentives can reduce attrition in intervention trials 216 and, once engaged, voucher incentive interventions for smoking cessation in pregnancy are both effective and acceptable to participants.…”
Section: Strengths and Limitationsmentioning
confidence: 98%
“…These findings are consistent with a recent Cochrane review which found that incentives have a small effect on attrition in research studies. 216 Costs varied in terms of what was reported (e.g. cost per participant or cost of implementing the entire intervention), what was provided (e.g.…”
Section: Incentives For Initiating and Continuing Smoking Cessationmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, both the intervention and "control" groups in studies had to be treated as multiple intervention groups (because both received incentives). Incentives for participation have evidence of effectiveness for attrition in studies 46 and are likely to interact with nonincentive components of the intervention, such as additional breastfeeding support. Assessment of effectiveness was also limited by inadequate comparator (nonincentivized) groups.…”
Section: Discussionmentioning
confidence: 99%